The Challenges of Teaching History and the Technification of the Profession in Primary Education: A Case Study at the National University (2024), Costa Rica - Gutiérrez Chavarría, Anthony (2025)
The objective of this article is to characterize the initial teacher training in the “Pedagogy with an emphasis on the first and second cycle of Basic General Education Program” and its connection with the development of historical time and history content in the curriculum. The theoretical foundation is based on the didactics of history, incorporating ideas from authors such as Joan Pagès, Antoni Santisteban, Carmen Escribano, and Jéssica Ramírez Achoy. Methodologically, a case study was conducted using a qualitative, socio-critical approach, involving two semi-structured interviews with faculty and six students, along with two questionnaires, one closed and one open, administered to the students.